ANALISIS DAN PERANCANGAN SISTEM INFORMASI PERBAIKAN DAN PERAWATAN SARANA PENUNJANG DI POLITEKNIK NEGERI SAMARINDA - Ansar Rizal; Karyo Budi Utomo (Just TI (Jurnal Sains Terapan Teknologi Informasi), 2016)
Proses of recording repairs and maintenance support facilities at the UPTMaintenance and Repair is done manually.Effects of manual recording results in less neat registration activities as well as repair and maintenance activities are not well documented. To answer of the above problems, it would require a means of support in creating a good administrative process and be able to document every incidence of repair and maintenance of facilities and infrastructure at the Polytechnic of Samarinda. Besides the optimization of service improvement it would require the presentation of reports online based,thus the distribution of reports can be quickly performed and consumed by those who need. Results of this research is the design of Repair and Maintenance Information Systems Support Facilities in Samarinda State Polytechnic. The planning process is done by observing the workflows that have been documented in the SOP combined with improvement ideas based on the analysis results. Keywords: Information sistim, repairs and maintenance, support facilities